2005
DOI: 10.1055/s-2005-864034
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Chemistry, and Reproductive Pharmacology of Asoprisnil and Related 11β-Benzaldoxime Substituted Selective Progesterone Receptor Modulators (SPRMs)

Abstract: Asoprisnil (J 867; benzaldehyde, 4-[(11beta, 17beta)-17-methoxy-17-(methoxymethyl)-3-oxoestra-4, 9-dien-11beta-yl]-, 1-oxime) is the prototype of a novel class 11beta-benzaldoxime-substituted selective progesterone receptor modulators (SPRMs) and the first-in-class SPRM to reach an advanced stage of clinical development for the treatment of uterine fibroids and endometriosis. This compound was selected in a drug discovery program aimed to identify progesterone receptor (PR) ligands with predominant agonist but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 50 publications
1
20
0
2
Order By: Relevance
“…The pharmacological effects of PRMs are, however, not purely antagonistic, nor is their effect restricted to the progesterone receptor itself. Some PRMs exert anti-estrogenic effects, either through partial progesterone receptor agonist activity, 6,7 or, exert these effects independently of the progesterone receptor itself, that is by upregulation of the androgen receptor response. 8,9 These PRM effects are evident as dose-dependent suppression of estrogen-induced mitotic activity, [10][11][12] and appearance of glandular secretory changes.…”
mentioning
confidence: 99%
“…The pharmacological effects of PRMs are, however, not purely antagonistic, nor is their effect restricted to the progesterone receptor itself. Some PRMs exert anti-estrogenic effects, either through partial progesterone receptor agonist activity, 6,7 or, exert these effects independently of the progesterone receptor itself, that is by upregulation of the androgen receptor response. 8,9 These PRM effects are evident as dose-dependent suppression of estrogen-induced mitotic activity, [10][11][12] and appearance of glandular secretory changes.…”
mentioning
confidence: 99%
“…It has high PR specificity with no antiglucocorticoid and marginal androgenic effects in humans (15). Asoprisnil shows a high degree of selectivity in the endometrium of animals and humans (15)(16)(17). In premenopausal women, asoprisnil is reported to suppress menstruation and induce mixed P4 agonist/antagonist effects on the glandular epithelium, stroma, and clusters of thick-walled arterial vessels in the endometrium without showing the endometrial hyperplasia indicative of unopposed estrogen effects (18).…”
mentioning
confidence: 99%
“…SPRMs are PR ligands that exert clinically relevant, tissue-selective P4 agonist, antagonist, partial, or mixed agonist/antagonist effects on various P4 target tissues in an in vivo situation depending on the biological action studied (15). Asoprisnil shows mixed P4 agonist/ antagonist and tissue-selective effects in various animal models (16,17). It has high PR specificity with no antiglucocorticoid and marginal androgenic effects in humans (15).…”
mentioning
confidence: 99%
“…One of the first was asoprisnil. Asoprisnil is a new SPRM with progesterone receptor agonist/antagonist properties, a lower level of gluco corticoid Editorial and estrogen receptor affinity as compared with mifepristone, and a marginal androgen receptor affinity [17,18]. Phase I studies with asoprisnil showed reversible suppression of menstruation and variable effects on ovulation.…”
Section: Asoprisnilmentioning
confidence: 99%